2020
DOI: 10.1021/acs.jpcc.0c02175
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Behavior and Optical Properties of a Fluorophore Dimer as a Model of Luminescent Centers in Carbon Dots

Abstract: The explanation of the origin of the fluorescence properties of carbon dots (CDs) represents an important task because of the great interest in the promising capabilities of these nanomaterials. 5-Oxo-1,2,3,5-tetrahydroimidazo-[1,2-α]-pyridine-7-carboxylic acid (IPCA), a molecular fluorophore, which is being created during the synthesis of CDs from citric acid and ethylenediamine, has been identified as an origin for the fluorescence of CDs. Using a combination of computational methods, we analyzed the UV abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 92 publications
4
53
0
Order By: Relevance
“…Vertical ionization energies and electron affinities of model structures representing carbon core, hydrophilic CD surface, and 5-oxo-1,2,3,5-tetrahydroimidazo­[1,2-α]­pyridine-7-carboxylic acid (IPCA) (see structures in Figure S21) were computed at the CAM-B3LYP/ aug -cc-pVTZ /CPCM , level of theory using the geometries optimized at the CAM-B3LYP/6-31G­(d)/CPCM level (coronene) or taken from references. , All calculations were performed with the Gaussian16 program…”
Section: Methodsmentioning
confidence: 99%
“…Vertical ionization energies and electron affinities of model structures representing carbon core, hydrophilic CD surface, and 5-oxo-1,2,3,5-tetrahydroimidazo­[1,2-α]­pyridine-7-carboxylic acid (IPCA) (see structures in Figure S21) were computed at the CAM-B3LYP/ aug -cc-pVTZ /CPCM , level of theory using the geometries optimized at the CAM-B3LYP/6-31G­(d)/CPCM level (coronene) or taken from references. , All calculations were performed with the Gaussian16 program…”
Section: Methodsmentioning
confidence: 99%
“…This approach focuses on CND molecular state which was largely confirmed in previous works [ 10 , 11 , 12 , 13 ]. The molecule-like model was also supported by quantum-chemistry calculations, where different N-doped aromatic moieties were considered, together with their aggregated forms, as the origin of the optical properties of bottom-up synthesized CNDs [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from this consideration, we hypothesized that the pyridinone molecules produced during the synthesis of CA and hydrazine, their aggregated forms or some polymeric structure derived by further reactions of the monomer units can be incorporated into the structure of the CDs and produce the optical features experimentally recorded. Indeed, if we consider the case of IPCA, a reaction of cyclization between CA and ethylene-diamine was hypothesized to produce the molecule that acts as a seed for the formation of the CDs and cause, with its aggregates, the excitation dependent emission features recorded in those systems [28,67,68]. In a similar way, we recently studied the formation of CZA in the synthesis of CA and urea (the reference system in the present study) and we demonstrated that the formation of various ionic species and different aggregates can explain the optical features of citric acid derived CDs [65,66,69,70].…”
Section: Discussionmentioning
confidence: 99%
“…None of the precursor vibrational modes were present in both the 1350-1400 and 1550-1600 cm −1 regions, whilst the pyridinone structure shows two bands at 1400 and 1580 cm −1 . To further explore the scenario, we considered for the Hy-CD case the formation of some typical aggregates already proposed for the CZA and IPCA systems [65][66][67][68][69], namely the parallel and anti-parallel stack dimers and the head-to-tail in plane dimer. We calculated the absorption spectra for the aggregate systems at a fixed distance between the monomer units, namely at 0.366 nm for the stack dimers and at 0.288 for the heat-to-tail dimers, assuming the same geometries of the parent CZA system.…”
Section: Er Review 11 Of 20mentioning
confidence: 99%